2015
DOI: 10.1002/clc.22382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Insurance Carrier, Prior Authorization, and Socioeconomic Status on Appropriate Use of SPECT Myocardial Perfusion Imaging in Private Community‐Based Office Practice

Abstract: Background:The impact of health insurance carrier and socioeconomic status (SES) on the adherence to appropriate use criteria (AUC) for radionuclide myocardial perfusion imaging (MPI) is unknown. Hypothesis: Health insurance carrier's prior authorization and patient's SES impact adherence to AUC for MPI in a fee-for-service setting. Methods: We conducted a prospective cohort study of 1511 consecutive patients who underwent outpatient MPI in a multi-site, office-based, fee-for-service setting. The patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A recent study showed that SPECT MPI is widely used for diagnostic and risk stratification purposes in the United States and patient’s socio-economic status did not significantly affect the use of SPECT MPI by physicians[15]. In the developing world several studies have shown the widespread use of SPECT MPI by physicians to aid in diagnosis in management[16,17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that SPECT MPI is widely used for diagnostic and risk stratification purposes in the United States and patient’s socio-economic status did not significantly affect the use of SPECT MPI by physicians[15]. In the developing world several studies have shown the widespread use of SPECT MPI by physicians to aid in diagnosis in management[16,17].…”
Section: Discussionmentioning
confidence: 99%
“…4850 Another strategy that has been considered is prior authorization, although a recent analysis on this strategy suggests no effect on the rate of inappropriate MPI among patients insured by private carriers as compared to Medicare which does not implement prior authorization measures. 51 …”
Section: Discussionmentioning
confidence: 99%
“…8,13,14 Between 9% and 44% of cardiac CT studies are inappropriate, [15][16][17] and 4% to 46% of SPECT studies have been classified as inappropriate. [18][19][20][21][22] No studies related to cardiac magnetic resonance imaging (CMR) were identified.…”
Section: Improving Appropriateness Of Cardiovascular Imaging Approprimentioning
confidence: 99%